1998
DOI: 10.1021/jp9811070
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio and RRKM Studies of the Reactions of C, CH, and 1CH2 with Acetylene

Abstract: We present ab initio calculations of geometries, energies, and normal mode frequencies for complexes and saddle points along the minimum energy reaction path for the reaction C + HCCH → C3H2 → C3H + H. We also present ab initio calculations along the minimum energy reaction path in the entrance channel for the reactions C + HCCH, CH + HCCH, and 1CH2 + HCCH. These results and those presented earlier by Walch are used to calculate rate constants for the reactions of C, CH, and 1CH2 with acetylene, using variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
124
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(149 citation statements)
references
References 38 publications
23
124
0
2
Order By: Relevance
“…19,20 More recently, such surfaces have been calculated with high-level ab initio methods by Schatz and co-workers for the three lowest energy surfaces 1 AЈ, 3 AЉ, and 1 AЉ of HNO. 21 The quasiclassical trajectory ͑QCT͒ calculations on these PESs agreed satisfactorily with the available experimental data. 22 Up to now, to the best of our knowledge, no accurate quantum mechanical calculations have been performed for the above-given reactions.…”
Section: Introductionsupporting
confidence: 71%
“…19,20 More recently, such surfaces have been calculated with high-level ab initio methods by Schatz and co-workers for the three lowest energy surfaces 1 AЈ, 3 AЉ, and 1 AЉ of HNO. 21 The quasiclassical trajectory ͑QCT͒ calculations on these PESs agreed satisfactorily with the available experimental data. 22 Up to now, to the best of our knowledge, no accurate quantum mechanical calculations have been performed for the above-given reactions.…”
Section: Introductionsupporting
confidence: 71%
“…In this study, the WP calculations using the MADWAVE3 code for the N + OH(v = 0, j = 0) → NO + H reaction have been performed for total angular momentum J ≥ 0, using an ab initio PES built by Guadagnini et al 20 State-to-state ICSs have been obtained for the first time using an accurate quantum mechanical method. The WP results have been compared with QCT calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The first ab initio potential energy surface (PES) for the N + OH → NO + H reaction was built by Guadagnini et al 20 This PES was based on complete active space self-consistent field (CASSCF)/internally contracted configuration interaction calculation and fitting of the 800 ab initio points obtained at the (multireference configuration interaction) MRCI/cc-pVTZ level. It was found that the N + OH → NO + H reaction has no barrier relative to the entrance channel and a double well along the reaction path, corresponding to HON and HNO configuration geometries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations